2013
DOI: 10.1186/1556-276x-8-524
|View full text |Cite
|
Sign up to set email alerts
|

Facile one-pot synthesis of polytypic CuGaS2 nanoplates

Abstract: CuGaS2 (CGS) nanoplates were successfully synthesized by one-pot thermolysis of a mixture solution of CuCl, GaCl3, and 1-dodecanethiol in noncoordinating solvent 1-octadecene. Their morphology, crystalline phase, and composition were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HRTEM), powder X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS), respectively. Crystalline structure analysis showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The first example of polytypism in these multinary systems was randomly discovered by Korgel et al during CuInS 2 nanodisks synthesis, where the WZ phase interfaces with significant chalcopyrite (CH) domains across (002) WZ /(112) CH stacking faults. Later, different researchers found that during the colloidal synthesis, at lower temperatures, the metastable wurtzite form of CuInS 2 occurs as nanoplates, but as the number of metal cations decrease with further progression of the reaction, WZ–ZB polytypism occurs in the system. , Furthermore, partial or complete substitution of Ga or Fe in the crystal lattice of CuInS 2 to form CuInGaS 2 (CIGS), CuGaS 2 , or CuInFeS 2 also results into the occurrence of WZ–ZB or WZ–CH polytypism. However, formation of branched morphologies or 1-D linear structures were not reported in Cu–In–Ga–S/Se systems.…”
mentioning
confidence: 99%
“…The first example of polytypism in these multinary systems was randomly discovered by Korgel et al during CuInS 2 nanodisks synthesis, where the WZ phase interfaces with significant chalcopyrite (CH) domains across (002) WZ /(112) CH stacking faults. Later, different researchers found that during the colloidal synthesis, at lower temperatures, the metastable wurtzite form of CuInS 2 occurs as nanoplates, but as the number of metal cations decrease with further progression of the reaction, WZ–ZB polytypism occurs in the system. , Furthermore, partial or complete substitution of Ga or Fe in the crystal lattice of CuInS 2 to form CuInGaS 2 (CIGS), CuGaS 2 , or CuInFeS 2 also results into the occurrence of WZ–ZB or WZ–CH polytypism. However, formation of branched morphologies or 1-D linear structures were not reported in Cu–In–Ga–S/Se systems.…”
mentioning
confidence: 99%
“…Figure 5c is a typical highresolution spectrum of Ga 2p 3/2 and Ga 2p 1/2 levels that shows peaks centred at 1118.1 eV and 1144.9 eV, respectively, with a peak separation of 26.8 eV indicative of trivalent gallium. 50,51 Deconvolution of the XPS high-resolution spectrum of the S 2p level (Fig. 5d) reveals two peaks centred at binding energies of 161.1 eV and 162.3 eV, corresponding respectively to the S 2p 3/2 and S 2p 1/2 levels with a peak separation of 1.2 eV that is consistent with metal sulfide material showing a sulphur (−II) oxidation state.…”
Section: Resultsmentioning
confidence: 57%
“…48 The high-resolution spectrum of Cu 2p reveals two peaks centred at binding energies of 931.7 eV and 951.6 eV that can be assigned to Cu 2p 3/2 and Cu 2p 1/2 levels, respectively, consistent with the standard separation of 19.9 eV for chalcopyrite Cu (I) species. [49][50][51] In addition, the Cu 2p satellite peak assigned to Cu (II) species, which is usually centred at ∼942 eV, 52,53 does not appear in the spectrum. Figure 5c is a typical highresolution spectrum of Ga 2p 3/2 and Ga 2p 1/2 levels that shows peaks centred at 1118.1 eV and 1144.9 eV, respectively, with a peak separation of 26.8 eV indicative of trivalent gallium.…”
Section: Resultsmentioning
confidence: 99%
“…For example, restricting to CuGaS 2 , there are reports of at least 8 different variations on the common dot, platelet, and rod shapes, starting from Cu 2-X S seeds. [21][22][23][24][25][26] This combination of compositional and morphological diversity suggests that the Cu 2-X S system may be ideal for tailoring Figure 1. Transmission Electron Microscopy (TEM) images of CuGaS 2 NR growth from aliquots taken at 0 s, 30 s, 1 min, 2 min, and 5 min.…”
Section: Introductionmentioning
confidence: 99%